2018
DOI: 10.1016/j.yjmcc.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized cyclic nucleotides have opposing effects on regulation of hypertrophic phospholipase Cε signaling in cardiac myocytes

Abstract: In cardiac myocytes activation of an exchange factor activated by cAMP (Epac) leads to activation of phospholipase Cε (PLCε)-dependent hydrolysis of phosphatidylinositol 4-phosphate (PI4P) in the Golgi apparatus a process critical for development of cardiac hypertrophy. Here we show that β-adrenergic receptor (βAR) stimulation does not stimulate this pathway in the presence of the broad spectrum phosphodiesterase (PDE) inhibitor IBMX, but selective PDE3 inhibition revealed βAR-dependent PI4P depletion. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…In previous work we found that either the Epac-selective cAMP analog, cpTOME, or forskolin stimulation of adenylate cyclase, activate PLCε-dependent Golgi PI4P hydrolysis in cardiac myocytes. Surprisingly, the βAR agonist isoproterenol (Iso), does not stimulate Golgi PI4P hydrolysis despite strongly stimulating cAMP production (Nash et al, 2018). As an explanation for this apparent paradox we demonstrated PLCε-dependent PI4P hydrolysis can be controlled by two distinct pools of cAMP delimited by distinct PDE isoforms.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work we found that either the Epac-selective cAMP analog, cpTOME, or forskolin stimulation of adenylate cyclase, activate PLCε-dependent Golgi PI4P hydrolysis in cardiac myocytes. Surprisingly, the βAR agonist isoproterenol (Iso), does not stimulate Golgi PI4P hydrolysis despite strongly stimulating cAMP production (Nash et al, 2018). As an explanation for this apparent paradox we demonstrated PLCε-dependent PI4P hydrolysis can be controlled by two distinct pools of cAMP delimited by distinct PDE isoforms.…”
Section: Introductionmentioning
confidence: 99%
“…PDE2 inhibition has been hypothesized to promote PKA-dependent phosphorylation and thereby inhibition of PLCε. Diminished PLCε-induced PI4P hydrolysis in the Golgi apparatus thus abrogates hypertrophic signalling [ 179 ].…”
Section: Role Of Pde2 In Cardiovascular Diseasementioning
confidence: 99%
“…Epac1 also promotes spontaneous diastolic Ca 2+ leak via CaMKII-dependent ryanodine receptors (RyR) hyperphosphorylation. Intriguingly, recent works suggested that intracellular β-ARs located at the Golgi could generate a specific pool of cAMP to stimulate a prohypertrophic Epac1/phospholipase C (PLC)ε signalling, which is scaffolded at the nuclear envelope of cardiomyocytes to the muscle-specific A-kinase anchoring (mAKAP) scaffolding protein [65,66] (Figure 2). Other studies demonstrated that an Epac1-PLC signalling could cause protein kinase D (PKD) activation and nuclear Ca 2+ increase via the perinuclear inositol-1,4,5-trisphosphate (IP3) receptor resulting in the activation of CaMKII-dependent epigenetic regulation involving HDAC4 and HDAC5 [7,64,67,68].…”
Section: Epigenetic Regulation Of Epac1 During Cardiac Remodellingmentioning
confidence: 99%